Accounting Information System: Cash Receipts at Zakat, Infaq and Sadaqah Institutions: Sistem Informasi Akuntansi: Penerimaan Kas di Lembaga Zakat, Infaq dan Shadaqah - Hanifa, Miftachul; Abidin, Fityan Izzah Noor (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this research was to find out the application of accounting information systems at zakat, infaq, shadaqah institutions in an effort to improve internal control of cash receipts at LAZISMU Sidoarjo. In this research, the main focus is the Technology Acceptance Model (TAM), which was introduced by Davis in 1989, which is an adaptation of the Theory of Reasoned Action (TRA) which is a theory to model user acceptance of technology. This research approach used a qualitative approach with primary data sources. Data collection was obtained from interviews, observations and documentation. data validity techniques with triangulation models. The results of the study stated that the application of accounting information systems in LAZISMU Sidoarjo Regency has used a central system, namely ZISKA software stands for (Zakat, Infaq, Sadaqah, and Humanity). The advantages of the system are more detailed. However, there are obstacles that occur such as network disruptions and to prevent the risk of data loss data backup is performed. To anticipate any recording errors on cash receipts, cross-checks and evaluation are conducted through meetings. The use of forms or documents has been numbered printed. Transparent financial statements to the public. Cash deposits to the bank are done every day and directly deposited on bank working days. There are some weaknesses in the internal control element.